Quantitative Real-Time RT-PCR Using Hybridization Probes and Imported Standard Curves for Cytokine Gene Expression Analysis. (November 2002) - Kühne, Benedikte Sabina; Oschmann, Patrick
Quantitative real-time or kinetic RTPCR is increasingly used for the quantification of specific mRNA targets, especially in clinical applications. To quantify the mRNA of cytokines and their receptors, which play important roles in the pathogenesis of autoimmune diseases such as multiple sclerosis, we have developed quantitative two-step RT-PCR assays for IL-4, IL-4R, IFN-γ, IFN-β, and the housekeeping gene porphobilinogen deaminase (PBGD). The LightCycler TM system was used to quantify the copy numbers with the sequence-specific hybridization probe detection format. The quantification was carried out on the basis of standard curves generated with external homologous plasmids for each different parameter in relation to the gene expression of PBGD. Therefore, this procedure represents a relative quantification method with external standards, as the standard curves were used to obtain an absolute value for the copy numbers of the targets and the reference (PBGD). The new software version 3.5 of the LightCycler system allows the construction of a single parameter-dependent plasmid standard curve for the quantification of unknown samples from different runs. Here we demonstrate how to achieve precise and reproducible quantification, even when using measurements from different PCR runs.